Input constraints handling in an MPC/feedback linearization scheme - Deng, Jiamei; Becerra, Victor M.; Stobart, Richard (Zielona Góra: Uniwersytet Zielonogórski)
The combination of model predictive control based on linear models (MPC) with feedback linearization (FL) has attracted interest for a number of years, giving rise to MPC+FL control schemes. An important advantage of such schemes is that feedback linearizable plants can be controlled with a linear predictive controller with a fixed model. Handling input constraints within such schemes is difficult since simple bound contraints on the input become state dependent because of the nonlinear transformation introduced by feedback linearization.
Keywords: predictive control; feedback linearization; neural networks; nonlinear systems; constraints